Levels of Oxidized LDL, Estrogens, and Progesterone in Placenta Tissues and Serum Paraoxonase Activity in Preeclampsia - Şerefden Açıkgöz; Ülkü Özmen Bayar; Murat Can; Berrak Güven; Görkem Mungan; Suat Doğan; Vildan Sümbüloğlu (Mediators of Inflammation)
In vitro literature studies have suggested that atherosclerotic oxidized low density lipoprotein (OxLDL) inhibits trophoblast invasion. The objective of this study was to determine the levels of OxLDL and to examine the relationship between antioxidative estradiol, estriol, and prooxidative progestin in normal and preeclamptic placental tissues and measure the serum activity of antioxidative paraoxonase (PON1). The study included 30 preeclamptic and 32 normal pregnant women. OxLDL was determined with ELISA, estradiol, unconjugated estriol, and progesterone that were determined with chemiluminescence method in placental tissues. Serum PON1 activity was determined with spectrophotometric method. Levels of OxLDL (), estriol (), estradiol (), and progesterone () were lower in the placental tissues of preeclamptic group compared to the normal pregnant women. Serum PON1 activity was higher in preeclamptic group () and preeclamptic group without intrauterine growth restriction () compared to normal pregnant women. Tissue estriol of preeclamptic group without/with IUGR (, ) was lower than the normal group. Results of our study suggest that the events leading to fetoplacental insufficiency lead to a reduction in the levels of estriol limit deposition of OxLDL in placental tissues. The serum PON1 activity is probably important in the inhibition of OxLDL in preeclampsia.